PENGARUH PEMAHAMAN KEAGAMAAN TERHADAP PENDIDIKAN: Kajian Empiris Pada Keluarga Pemulung - Setiono Setiono (TASÂMUH, 2016)
Family is the main environment for children to make social interaction. The family has the most important role in building children’s personality. In the family environment, a child will learn knowledge system of norms accepted and recognized by society. Even in education, family should direct their children to get good education since every citizen has right to have education as good as possible. Furthermore, formal education is understood as an education, in which the children are taught to write, read, and count. The school is also good place for educating children and developing their talents. On the other hand, informal education is one obtained since they were born or they are in childhood. This informal education is about religion, moral, ethic, behavior, discipline, honesty, self-reliance and responsibility. The poverty of family is not barrier to get education. For rag picker family, formal education is one based on curriculum, having structure that is taken process through socialization of education in the school. Otherwise, informal education is related to other social regulation such as religion, economy, ethic and family.